Lagrangian Modeling of Arctic Ocean Circulation Pathways: Impact of Advection on Spread of Pollutants. Issue 4 (25th April 2018) - Kelly, S.; Popova, E.; Aksenov, Y.; Marsh, R.; Yool, A.
Abstract: Sea‐ice‐free summers are projected to become a prominent feature of the Arctic environment in the coming decades. From a shipping perspective, this means larger areas of open water in the summer, thinner and less compact ice all year round, and longer operating seasons. Therefore, the possibility for easier navigation along trans‐Arctic shipping routes arises. The Northern Sea Route (NSR) is one trans‐Arctic route, and it offers a potential 10 day shortcut between Western Europe and the Far East. More ships transiting the NSR means an increased risk of an accident, and associated oil spill, occurring. Previous research suggests that current infrastructure is insufficient for increased shipping. Therefore, should an oil spill occur, the window for a successful clean‐up will be short. In the event of a failed recovery, the long‐term fate of the unrecovered pollutants must be considered, at least until the next melt season when it could become accessible again. Here we investigate the role of oceanic advection in determining the long‐term fate of Arctic pollutants using a high‐resolution ocean model along with Lagrangian particle‐tracking to simulate the spread of pollutants. The resulting "advective footprints" of pollutants are proposed as an informative metric for analyzing such experiments. We characterize the circulation along different parts of the NSR, defining three main regions in the Eurasian Arctic, and relate the distinctive circulation pathways of each to the long‐term fate of spilled oil. We conclude that a detailed understanding of ocean circulation is critical for determining the long‐term fate of Arctic pollutants. Plain Language Summary: The Earth's climate is changing and the Arctic Ocean is projected to experience ice free summers within decades. This would enable more commercial shipping, which in turn makes an Arctic shipping accident more likely. This could lead to oil (or other pollutants) being spilled into the ocean. Because of the harsh Arctic environment, an oil spill may not be successfully recovered, so we need to consider where it will go in the following months and years. We released virtual "particles" into a computer model of the ocean and tracked their progress for 2 years. In this time, particles traveled, on average, 1, 223 km. This demonstrates that pan‐Arctic modeling is needed in the event of an unrecovered pollutant spill. Unrecovered oil from one season may be accessible the next spring. By analyzing the spread of our particles, we found that on average 676, 917 km 2 would need to be searched to find it, but that this is highly dependent on where the spill occurs. Finally, we noted that in some places, particularly the Barents Sea, there was a risk that spilled pollutants could become entrained into deep water, rendering them irrecoverable. Key Points: Pan‐Arctic modeling of advective pathways is necessary to understand the long‐term (2 years) fate of pollutants spilled in the Arctic Ocean Long‐term fate of pollutants dependent on where the spill occurs: the Northern Sea Route can be split into three main regimes Subduction into deep water could render pollutants irrecoverable. This is a risk especially for spills occurring in the Barents Sea